2016
DOI: 10.1007/s00383-016-3912-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of calretinin and role of age in the diagnosis of Hirschsprung disease

Abstract: We analyzed 91 patients. Results of the RSB: 40 HD (44 %), 34 no Hirschsprung (37.4 %) and 17 NC (18.7 %). Sensitivity = 97.5 %, specificity = 97.1 %, not including the NC (1 false positive, 1 false negative). Results depending on the staining: ACE (n = 58) (%) ACE + C (n = 33) (%) p Sensitivity 96 100 1 Specificity 94.7 100 1 NC 24.1 9.1 0.077 Results depending on the age: <1.5 m (n = 27) (%) >1.5 m (n = 64) (%) p Sensitivity 92.3 100 0.325 Specificity 100 96.8 1 NC 40.7 9.4 0.001 CONCLUSION: Calretinin decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…When 9 of the biopsies obtained from 24 patients included in the study, which were considered as insufficient material, were not included in the evaluation, the specificity and sensitivity of SRB from 15 patients was found to be 100%. It has been reported that the sensitivity of SRB in the diagnosis of HD is 88-93% and its specificity is 95-99% (22,23,(28)(29)(30). In the study of Nicole, no false negative or false positive results were reported, similar to our study (28).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…When 9 of the biopsies obtained from 24 patients included in the study, which were considered as insufficient material, were not included in the evaluation, the specificity and sensitivity of SRB from 15 patients was found to be 100%. It has been reported that the sensitivity of SRB in the diagnosis of HD is 88-93% and its specificity is 95-99% (22,23,(28)(29)(30). In the study of Nicole, no false negative or false positive results were reported, similar to our study (28).…”
Section: Discussionsupporting
confidence: 89%
“…When the studies in the literature are examined, different results draw attention when the diagnostic feature of SRB according to age groups is evaluated. While some studies reported that there was no difference in the diagnostic yield of SRB between age groups, several studies reported that insufficiency rate was higher in infants younger than 1.5 months compared to infants older than 1.5 months (5,22). In another study, it was reported that the tissue adequacy rate was higher in babies older than one year compared to babies older than one year old (25).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Calretinin immunohistochemistry was introduced in 2009 and replaced acetylcholinesterase histochemistry in many laboratories, where the standard approach has become to review both hematoxylin-and-eosin (H&E)stained paraffin sections and at least 1 calretinin-immunostained section from the same biopsy. 5,54 In contrast with acetylcholinesterase histochemistry, calretinin-positive mucosal innervation is typically absent in the aganglionic rectal biopsies and, for most patients, correlates extremely well with other diagnostic findings of HSCR. Routine use of calretinin immunohistochemistry has lowered the threshold for how much submucosal sampling is considered adequate and has probably led to diagnoses that would have not been possible with H&E-stained sections alone.…”
Section: Recent Changes In the Diagnostic Approach To Hscr May Increamentioning
confidence: 96%
“…In many laboratories, !50 hematoxylin-and-eosin (H&E)stained sections are routinely evaluated, and it is not uncommon to exhaust paraffin-embedded tissue in an effort to exclude a ganglion cell. 1 Reported rates of inconclusive biopsy results range from 11% to 38%, with ''inadequate submucosa'' cited as a frequent explanation (see de Haro Jorge et al 2 and references therein). Numerous ancillary histological methods have been reported to facilitate diagnosis, most of which rely on immunohistochemical resolution of ganglion cells.…”
Section: Introductionmentioning
confidence: 99%